Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Physics-informed graph inference and prediction for global state estimation in water distribution networks - Yacan Man; Xiao Zhou; Wenchong Tian; Rui Yuan; Kuizu Su; Zhiguo Yuan (Water Research, 2026)

Heterogeneous rock abundances in the lunar subsurface revealed by cold-spot craters - Yizhen Ma; Zhiyong Xiao; Yichen Wang; Yiren Chang; Rui Xu; Yan Su (Icarus, 2026)

A dual-state emission NIR fluorescent sensor for intelligent dual-analyte detection and multisite imaging: From N2H4/ClO− and fingerprints to living cells and organisms - Su-qian Cai; Bo-wen An; Rui-yong Jiang; Shang-wei Yuan; Xin Xiao (Analytica Chimica Acta, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

A COF-spaced Plasmon-enhanced fluorescent nanocomposite for ultrasensitive and on-site dual-modality lateral flow immunoassay - Han Han; Junhua Su; Zhenzhen Liu; Zijin Tong; Lei Wu; Shihui Zhu; Wentao Zhao; Baohua Zhao; Rui Xiao (Chemical Engineering Journal, 2026)

Electronic structure engineered Fe-ZnO@au-DTNB nanotags for ultrasensitive SERS-based lateral flow immunoassay - Renjie Xiong; Junhua Su; Shizhe Wang; Zijin Tong; Renlong Zhu; Yufei Liu; Rui Xiao (Chemical Engineering Journal, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Improving multi-step water demand forecasting performance: Static, past, future, and periodic feature importance - Rui Yuan; Yacan Man; Kuizu Su; Xiao Zhou; Shuming Liu (Journal of Water Process Engineering, 2026)

Multi-Target Water Demand Forecasting with Graph Neural Networks: A Comparative Study - Yacan Man; Xiao Zhou; Rui Yuan; Kuizu Su; Shuming Liu (Water Resources Management, 2026)

Evolution of soil arching under different initial water-saturation conditions via coupled SPH-DEM method - Rui-Xiao Zhang; Dong Su; Xiang-Sheng Chen; Xiu-Song Shi; De-Jin Zhang (Computers and Geotechnics, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Theoretical calculation model of the soil arching effect considering tunnel influence - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Xiang-Sheng Chen (Tunnelling and Underground Space Technology, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Ultrafast and ultrastable Na-ion storage in interface engineered MoS2/MXene nanohybrids with nanoconfinement for high-performance sodium-ion capacitors - Yuanhua Xiao; Qingling Le; Yang Kong; Wendi Lv; Dangcheng Su; Xianhong Rui; Shuyan Yu; Aiqing Zhang; Junhong Zhao; Qingxiang Yang; Qingxian Jin; Yujie Zheng; et al. (Chemical Engineering Journal, 2025)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Effect of surcharge width on evolution of soil arching for active and passive trapdoor - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin (European Journal of Environmental and Civil Engineering, 2024)

Anthropogenic cycles of praseodymium in China: 2000–2020 - Shijiang Xiao; Yong Geng; Xue Rui; Ziyan Gao; Chang Su; Tianli Yao; Chen Zhong (Resources Policy, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Soil arching in ground with tunnel: Effect of distance between tunnel and trapdoor - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Hao Xiong; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Investigation of the soil arching evolution in the ground with or without a tunnel - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Tai-Feng Zhu; Guoping Lei; Xiang-Sheng Chen (Transportation Geotechnics, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

Effects of oxytetracycline on plant growth, phosphorus uptake, and carboxylates in the rhizosheath of alfalfa - Zekun Zhang; Rui Su; Chao Chang; Xiao Cheng; Qi Peng; Hans Lambers; Honghua He (Plant and Soil, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Sharing of Genetic Association Signals by Age-Related Macular Degeneration and Alzheimer’s Disease at Multiple Levels - Handan Tan; Meng Lv; Xiao Tan; Guannan Su; Rui Chang; Peizeng Yang (Molecular Neurobiology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Neuroprotective effect of miR-410-3p against sevoflurane anesthesia-induced cognitive dysfunction in rats through PI3K/Akt signaling pathway via targeting C–X–C motif chemokine receptor 5 - Rui Su; Ping Sun; Dianhong Zhang; Wei Xiao; Chun Feng; Liang Zhong (Genes & Genomics, 2019)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

Long-Term Effectiveness of Total Hip Replacement with the Collum Femoris Preserving Prosthesis - Rui-jin You; Wen-zhong Zheng; Kun Chen; Hong-sheng Lv; Dian-feng Huang; Yi-zeng Xiao; De-yu Yang; Zhai-quan Su (Cell Biochemistry and Biophysics, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Transcriptome profiling of biliary atresia from new born infants by deep sequencing - Jie Xiao; Su-yun Xia; Yun Xia; Qiang Xia; Xiang-rui Wang (Molecular Biology Reports, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Impacts of Transportation Routes on Landscape Diversity: A Comparison of Different Route Types and Their Combined Effects - Shiliang Su; Rui Xiao; Delong Li; Yi’na Hu (Environmental Management, 2014)

Spatially Varying Determinants of Farmland Conversion Across Qiantang Watershed, China - Shiliang Su; Rui Xiao (Environmental Management, 2013)

Spatial analysis of phytoplankton patterns in relation to environmental factors across the southern Taihu basin, China - Rui Xiao; Shiliang Su; Anas Ghadouani; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Multi-scale spatial determinants of dissolved oxygen and nutrients in Qiantang River, China - Shiliang Su; Rui Xiao; Xiangyang Xu; Zhonghao Zhang; Xiaoya Mi; Jiaping Wu (Regional Environmental Change, 2013)

Optimization of biotransformation from phytosterol to androstenedione by a mutant Mycobacterium neoaurum ZJUVN-08 - Xiao-yan Zhang; Yong Peng; Zhong-rui Su; Qi-he Chen; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2013)

Geospatial assessment of agroecosystem health: development of an integrated index based on catastrophe theory - Shiliang Su; Zhonghao Zhang; Rui Xiao; Zhenlan Jiang; Tao Chen; Limin Zhang; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Assessing land ecological security in Shanghai (China) based on catastrophe theory - Shiliang Su; Dan Li; Xiang Yu; Zhonghao Zhang; Qi Zhang; Rui Xiao; Junjun Zhi; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2011)